Daily quality control in computed radiography mammography using the manufacturer phantom - Jakubiak, Rosangela R.; Messias, Pricila C.; Oliveira, Carlla M. (Revista Brasileira de Física Médica, 2015)
The quality control (QC) in mammography system involves a large amount of test tools, which implies a large space for storage and a high number of exposure. This work describes a QC system using a phantom, Fuji Computed Radiography (FCR) One Shot Phantom M Plus, that evaluates several parameters with just one exposure. The software offers tests with annual, semi-annual, quarterly, weekly and daily periodicity, and analyzes the conformities of the mammography equipment, image plate and cassettes. Because of the high number of tests, it was evaluated the daily test only for seven months in two mammography equipments. The test, through the software and its image, allows the analysis of ten parameters in QC. The evaluation of these parameters was realized by the average of the values provided by the software. Only one of the evaluated items showed not conformity, but this was observed and the necessary corrections were realized. The monitoring of use of FCR Mammography QC software with the FCR One Shot Phantom M Plus was realized and through this we could investigate that the quality program provided by the system is appropriate for the radiology services that has the Fuji Computed Radiography system.